Opinions on Youth Suicide Risk Screening from Individuals with Neurodevelopmental Disabilities and Their Therapists: A Pilot Study - Annabelle M. Mournet; Rachel Greenbaum; Audrey Thurm; Laura Weinheimer; Nathan J. Lowry; Jeffrey A. Bridge; Maryland Pao; Lisa M. Horowitz (MDPI AG, 2021)
Background: Individuals with neurodevelopmental disorders (NDD) are at increased risk for suicide, yet little work has been done to address the specific needs for this population. Specifically, there are no validated suicide risk screening instruments and processes for individuals with NDD; this study aimed to assess the opinions of individuals with NDD and their therapists on suicide risk screening in order to inform best practices for screening. Method: A pilot study was launched to qualitatively evaluate processes and instruments that may be used in future studies on suicide screening risk in NDDs. Participants and their therapists were surveyed after filling out suicide risk screening instruments and provided qualitative feedback on their opinions of screening for suicide risk. Results: Most participants (9/15) reported positive experiences of being screened for suicide risk. Additionally, almost all therapists (14/15) were in support of suicide risk screening. Several themes, such as interpersonal benefits, emerged as reasons for supporting screening. Conclusions: The findings from this pilot study provide initial qualitative evidence that many individuals with NDD and their therapists would be comfortable with and are in support of suicide risk screening for this population. Screening tools to guide clinicians on how to ask about suicide risk are needed and appear to be desired by clinicians on the frontlines of mental health treatment for people with NDD.